'Beauty is in the eye of the beer holder': People who think they are drunk also think they are attractive. (15th May 2012) - Bègue, Laurent; Bushman, Brad J.; Zerhouni, Oulmann; Subra, Baptiste; Ourabah, Medhi
<x xml:space="preserve">Abstract</x> This research examines the role of alcohol consumption on self‐perceived attractiveness. Study 1, carried out in a barroom (N= 19), showed that the more alcoholic drinks customers consumed, the more attractive they thought they were. In Study 2, 94 non‐student participants in a bogus taste‐test study were given either an alcoholic beverage (target BAL [blood alcohol level]= 0.10 g/100 ml) or a non‐alcoholic beverage, with half of each group believing they had consumed alcohol and half believing they had not (balanced placebo design). After consuming beverages, they delivered a speech and rated how attractive, bright, original, and funny they thought they were. The speeches were videotaped and rated by 22 independent judges. Results showed that participants who thought they had consumed alcohol gave themselves more positive self‐evaluations. However, ratings from independent judges showed that this boost in self‐evaluation was unrelated to actual performance.